An Analysis of Digital Image Processing Techniques (International Journal of Innovative Research in Computer Science & Technology, 2022)
Image processing is process of modifying  nature of an image in order to improve its visual  information about human interpretations & autonomously  machine detection. Digital image processing is subset of  electronics realm in which a picture is converted to an array  of small integers known as pixels that reflect a physical  attribute such as particular circumstance & data in digital  memory before being h&led by a computer equipment.  two primary application areas for digital image processing  techniques that have generated attention are enhancing  pictorial information for human interpretation & processing image data for storage, transmission, & representation for autonomous machine perception. Edges  define boundaries, & edge recognition is one of most  difficult tasks in image processing.. As a result, it is a basic  issue in image processing. This article looks at many  stages of digital picture processing. This study may be  exp&ed in future by applying similar methods to a variety  of digital pictures.
Keywords: Image recognition; Image retrieval; Image processing; Picture; Quality